1992
DOI: 10.1016/s0886-3350(13)80931-5
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous deposits on explanted intraocular lenses

Abstract: An immunohistochemical study of type I collagen in deposits on the surface of two intraocular lenses (IOLs) explanted from human eyes was conducted. Type I collagen-immunoreactive proteinaceous deposits with cells were found around the haptics of an iris-supported IOL. A few such deposits and what appeared to be macrophages were observed on the optic. A few cells (presumably macrophages and giant cells) were observed on a posterior chamber IOL, whereas proteinaceous deposits that reacted positively to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The prolyl 4-hydroxylase-positive cells on the posterior surface of the IOL in case 2 were considered to be lens epithelial cells that had grown between the posterior surface of the IOL and the posterior capsule. We previously detected various collagen types and fibronectin on IOLs explanted from human eyes with pathological conditions such as proliferative vitreoretinopathy and diabetic retinopathy and from rabbit eyes free of ocular fundus complications [15,26,28,29,30,32,34]. The present findings confirm that collagen-producing cells with immunoreactivity for prolyl 4-hydroxylase adhere to the surfaces of PC-IOLs, where immunolocalization of procollagen does not indicate the presence of collagen-synthesizing cells because procollagen peptides are easily secreted under physiological ascorbate-rich conditions [27].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The prolyl 4-hydroxylase-positive cells on the posterior surface of the IOL in case 2 were considered to be lens epithelial cells that had grown between the posterior surface of the IOL and the posterior capsule. We previously detected various collagen types and fibronectin on IOLs explanted from human eyes with pathological conditions such as proliferative vitreoretinopathy and diabetic retinopathy and from rabbit eyes free of ocular fundus complications [15,26,28,29,30,32,34]. The present findings confirm that collagen-producing cells with immunoreactivity for prolyl 4-hydroxylase adhere to the surfaces of PC-IOLs, where immunolocalization of procollagen does not indicate the presence of collagen-synthesizing cells because procollagen peptides are easily secreted under physiological ascorbate-rich conditions [27].…”
Section: Discussionsupporting
confidence: 71%
“…In previous immunohistochemical studies, we found that proteinaceous deposits on the surfaces of explanted polymethylmethacrylate (PMMA), IOLs contained collagen types I and IV, cellular fibronectin, and vitronectin [26,28,29]. Deposits immunoreactive for collagen types I, III, and IV and cellular fibronectin were also observed on PMMA and silicone IOLs that were experimentally implanted in rabbit eyes [32,33].…”
Section: Introductionmentioning
confidence: 86%
“…The mean collagen produced by proliferating lens epithelial cells around the IOL may also be altered to types I and III, as the condition for proliferation of cells on IOL optics resembles that of the cell culture, i.e., the growth of cells on a plastic material. We previously detected immunohistochemically the deposition of collagen types I, III and IV and of cellular fibronectin, accompanied by adhesion of macrophages foreignbody giant cells and presumed lens epithelial cells on PMMA IOLs that were explanted from patients during vitreous surgery performed for PVR or PDR (Saika et al, 1992(Saika et al, , 1993. The growth factor components found in the intraocular fluid were elevated under such conditions (Connor et al, 1989 ;GonzalezAvila et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Ishibashi and coworkers (1994) detected collagen types I and III, the major components of collagenous connective tissue, in opacifications of human posterior capsules by immunoelectron microscopy. We have detected deposition of various extracellular matrix components, including collagen types I and IV and cellular fibronectin, on the surfaces of IOLs explanted from patients or rabbits (Saika et al, 1992(Saika et al, , 1993(Saika et al, , 1997a(Saika et al, , 1997b. Therefore, we believe that these matrix proteins are the components accumulated on the capsules.…”
Section: Introductionmentioning
confidence: 95%